Editorial - Soares, Adriana Benevides; Feijoo, Ana Maria Lopes Calvo de; Ewald, Ariane Patrícia; Mancebo, Deise; Prestrelo, Eleonôra Torres; Soares, Jorge Coelho; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2011)
Adriana Benevides Soares, Ana Maria Lopes Calvo de Feijoo, Ariane Patrícia Ewald, Deise Mancebo, Eleonôra Torres Prestrelo, Jorge Coelho Soares, Rita Maria Manso de Barros